Trends in the applications of terahertz radiation in oral oncology treatments - Marwan Al-Raeei (Oral Oncology Reports)
In Terahertz radiation, known as THz-rays, falls within a special range of frequencies in the electromagnetic spectrum, from 0.1 to 10 THz. This radiation has unique benefits for medical imaging, security screening, and non-destructive testing. Their capacity to pass through non-metallic substances and produce detailed images of objects not visible to the naked eye is highly valuable in industries like pharmaceuticals, telecommunications, and healthcare. Continual research is focused on utilizing terahertz technology for various purposes, with the potential for groundbreaking advancements in communication, healthcare, and security. This study highlights the potential benefits of using terahertz radiation to treat dental tumors. The research investigates how applying different energy levels can effectively target and treat these tumors in the mouth. By examining the principles of terahertz radiation and its effects on dental tumors, we aim to offer valuable insights that could transform the treatment of these conditions in the future. Through our analysis and experiments, we aim to demonstrate the efficacy and advantages of using terahertz radiation in dentistry. In conclusion, the utilization of terahertz radiation in oral tumor treatments poses both promise and challenges in the field of oral oncology. While terahertz radiation offers unique advantages such as low energy levels and coherence, it is also hindered by limitations such as low power output, high cost, and restricted range. Addressing these limitations through further research, collaboration, and expert oversight is essential to optimize the effectiveness of terahertz radiation in treating oral tumors. With advancements in technology and a focus on safety measures, terahertz radiation has the potential to revolutionize the future of oral oncology treatments.